(untitled) (Revista da Faculdade de Direito, Universidade de São Paulo, 2005)
The main scope of the article is the analysis of the fees, here realized as a tax collected as retribution to the public, specific and divisible services in Brazilian Constitutional Tax System. First of all, we have done a study of the historical evolution of the fees in the doctrine and in the law, taking above all the Brazilian Constitutions. Next, the tax norm’s describers (hypothesis) and prescribers (consequence) were examined, taking into account the applicability of the ability to pay principle and the economic use of taxes. Ultimately, the divisibility and specificity as characters of public services were scrutinized, bringing some conclusions about this theme.